(untitled) (International Journal of Engineering and Computer Science, 2019)
Smoking is a practice in which a substance most commonly called cannabis is burnt and the smoke tasted or inhaled. The aim of this work is to design software that will predict the negative impact of marijuana smoking on consumers. This will help in recognizing the consequences of smoking marijuana and abuse on physical and mental health as well as socio-occupational life and also act as a necessary step for initiating appropriate action to reduce the harm/danger from smoking. This work was motivated by the observed and anticipated negative health burden with its concomitant socio- economic consequences which the nation is bound to face, if systematic efforts are not made now to control the growing problem of marijuana smoking. The methodologies for the execution of this research work were the statistical analysis of a sample population of people treated at the Imo State teaching hospital (IMSUTH from diseases emanating from marijuana smoking using Statistical Packages for Scientific Studies (SPSS) and deployment of the relevant coefficients from the analysis to develop a systematic forecasting software model used in simulating for the next 30 years. The simulation is intended to be predictive and to enable policy makers to see the impact and dangers of marijuana smoking between now and the next 30 years if current abuse is not controlled .That is the number of smokers likely to contact liver, brain and related diseases and who are most likely to die from these diseases. The software provides approximate prediction of likely deaths that may occur via diseases such as: liver, brain damage, heart and hypertension